A Comparative Study of the RAPINA and the Virus‐Neutralizing Test (RFFIT) for the Estimation of Antirabies‐Neutralizing Antibody Levels in Dog Samples. (12th November 2016) - Manalo, D. L.; Yamada, K.; Watanabe, I.; Miranda, M. E. G.; Lapiz, S. M. D.; Tapdasan, E.; Petspophonsakul, W.; Inoue, S.; Khawplod, P.; Nishizono, A.
Summary: The mass vaccination of dogs against rabies is a highly rational strategy for interrupting the natural transmission of urban rabies. According to the World Organization for Animal Health (OIE) and the World Health Organization (WHO), the immunization of at least 70% of the total dog population minimizes the risk of endemic rabies. Knowledge of the virus‐neutralizing antibody (VNA) level against the rabies virus (RABV) is required to evaluate protective immunity and vaccine coverage of dogs in the field. The rapid focus fluorescent inhibition test (RFFIT) and the fluorescent antibody virus neutralization (FAVN) test are recommended by OIE and WHO to determine the VNA levels in serum. However, these tests are cell culture based and require the use of live viruses and specialized equipment. The rapid neutralizing antibody test (RAPINA) is a novel, immunochromatographic test that uses inactivated virus to estimate the VNA level qualitatively. It is a simple, rapid and inexpensive, although indirect, assay for the detection of VNA levels. The RAPINA has shown good positive and negative predictive values and a high concordance with the RFFIT results. In this study, we compared the performance of the two tests for evaluating the vaccination status of dogs in the Philippines, Thailand and Japan. A total of 1135 dog sera were analysed by the RAPINA and compared to the VNA levels determined by the RFFIT. The overall positive and negative predictive values of the RAPINA were 96.2–99.3% and 84.5–94.8%, respectively, with a concordance (kappa) of 0.946–0.97 among the three countries. The RAPINA results were highly homologous and reproducible among different laboratories. These results suggest that this test is appropriate to survey vaccination coverage in countries with limited resources.